Predictors of dysphagia screening and pneumonia among patients with intracerebral haemorrhage in China: a cross-sectional hospital-based retrospective study - Yong-Jun Wang; Hong-Qiu Gu; Zi-Xiao Li; Xing-Quan Zhao; Kai-Xuan Yang; Yong-Mei Deng; Jin-Ju Sun (BMJ Open)
Objectives This study aimed to investigate factors associated with undergoing dysphagia screening (DS) and developing pneumonia, as well as the relationship between DS and pneumonia in patients with intracerebral haemorrhage (ICH).Design Our study was a cross-sectional hospital-based retrospective study.Study design and settings We derived data from the China Stroke Centre Alliance, a nationwide clinical registry of ICH from 1476 participating hospitals in mainland China. To identify predictors for pneumonia, multivariable logistic regression models were used to identify patient characteristics that were independently associated with DS and pneumonia.Participants We included 31 546 patients in this study with patient characteristics, admission location, medical history, hospital characteristics and hospital grade from August 2015 to July 2019.Primary and secondary outcome measures The primary outcomes were DS and pneumonia during acute hospitalisation.Results In total, 25 749 (81.6%) and 7257 (23.0%) patients with ICH underwent DS and developed pneumonia. Compared with patients without pneumonia, those who developed pneumonia were older and had severe strokes (Glasgow Coma Scale 9–13: 52.7% vs 26.9%). Multivariable analyses revealed that a higher pneumonia risk was associated with dysphagia (OR, 4.34; 95% CI, 4.02 to 4.68), heart failure (OR, 1.85; 95% CI, 1.24 to 2.77) and smoking (OR, 1.12; 95% CI, 1.12 to 0.20). DS was associated with lower odds of pneumonia (OR, 0.65; 95% CI, 0.44 to 0.95).Conclusion Our findings further confirm that dysphagia is an independent risk factor for pneumonia; one-fifth of patients with ICH did not undergo DS. However, comprehensive dysphagia evaluation and effective management are crucial. Nursing processes ensure the collection of complete and accurate information during evaluation of patients. There is a need to increase the rate of DS in patients with ICH, especially those with severe stroke or older. Further, randomised controlled trials are warranted to determine the effectiveness of DS on clinical outcomes.